DARC on RBC limits lung injury by balancing compartmental distribution of CXC chemokines - Reutershan, Joerg; Harry, Brian; Chang, Daniel; Bagby, Gregory J.; Ley, Klaus (European Journal of Immunology, 2009)
The Duffy antigen receptor for chemokines (DARC) has a high affinity for CC and CXC chemokines. However, it lacks the ability to induce cell responses that are typical for classical chemokine receptors. The role of DARC in inflammatory conditions remains to be elucidated. We studied the role of DARC in a murine model of acute lung injury. We found that in Darc-gene-deficient (Darc-/-) mice, LPS-induced PMN migration into the alveolar space was elevated more than twofold. In contrast, PMN adhesion to endothelial cells and within the interstitial space was reduced in Darc-/- mice. Darc-/- mice also exhibited increased microvascular permeability. Elevated PMN migration in Darc-/- mice was associated with increased concentrations of two essential CXCR2 ligands, CXCL1 and CXCL2/3 in the alveolar space. In the blood, CXCL1 was mostly associated with RBC in WT mice and with plasma in Darc-/- mice. We found that DARC on RBC prevented excessive PMN migration into the alveolar space. In contrast, DARC on non-hematopoietic cells appeared to have only minor effects on leukocyte trafficking in this model. These findings show how DARC regulates lung inflammation by controlling the distribution and presentation of chemokines that bind CXCR2. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute lung injury; Chemokines; Inflammation; Polymorphonuclear leukocytes; Transmigration